LEGALITAS KONTRAK PERDAGANGAN SECARA ELEKTRONIK DITINJAU DALAM KITAB UNDANG-UNDANG HUKUM PERDATA - Fakhry Firmanto; Hafiz Sutrisno; Aminoel Akbar Novi Maimory (Jurnal Pahlawan, 2023)
The purpose of this study is to understand and know about the legality of electronic trade contracts in the Civil Code and the legal consequences if the electronic trade contracts are made illegally. The research method used in this paper is a normative legal research method with a statutory and conceptual approach. The results of this paper show that the legality of electronic commerce contracts is contained in the provisions of Article 1320 of the Civil Code, namely the agreement of the parties; the ability of the parties to do legal actions; a certain subject matter; and a non-prohibited cause and legal consequences if an electronic trade contract or e-contract is invalid is null and void by law if it is not in accordance with the provisions of Article 1320 of the Civil Code.